The Impact of COVID-19 Pandemic on The Construction Projects in Indonesia: Identifying the Risks from the Stakeholders’ Perspective - Gina Cynthia Raphita Hasibuan; Indra Jaya; M. Thoriq Al Fath (Talenta Publisher, 2023)
Covid-19, which is declared as a pandemic by the World Health Organisation (WHO) on March 11 2020 has significant impacts in many sectors around the world. Nevertheless, there is a lack of research which analyses the impact of Covid-19 in the construction projects risks in developing countries. Given the lack of research related to the construction projects risks due to Covid-19, the overall aim of the study is to identify and classify the risk in a construction project as a result of Covid-19 Pandemic in Indonesia. The methodology which is used in this study is by implementing the questionnaire approach with the targets from the related construction industry stakeholders. The findings identified five risks which have the highest possibility to occur in a construction project as a result of Covid-19, in which the highest risk is delayed funding on construction project design (Score: 0,2523) while the lowest risk is unknown threat or vandalism from the neighborhood gangster (score: 0,0136). Further study will focus on the way in which we could develop a new framework model for risk management and preventive measures of these risks adjusted to Covid-19 impact.